[3H]‐L685, 458 Binding Sites are Abundant in Multiple Peripheral Organs in Rats: Implications for Safety Assessment of Putative γ‐Secretase Targeting Drugs. (4th July 2014) - Yang, Zhi‐Ying; Li, Jian‐Ming; Xiao, Ling; Mou, Lin; Cai, Yan; Huang, He; Luo, Xue‐Gang; Yan, Xiao‐Xin
Abstract γ‐Secretase is a multimeric enzyme complex that carries out proteolytic processing to a variety of cellular proteins. It is currently explored as a therapeutic target for Alzheimer's disease (AD) and cancer. Mechanism‐based toxicity needs to be thoroughly evaluated for γ‐secretase inhibitory and/or modulatory drugs. This study comparatively assessed putative γ‐secretase catalytic sites in rat peripheral tissues relative to brain and explored an effort of its pharmacological inhibition on hair regeneration. Using [3H]‐labelled L685, 458, a potent γ‐secretase inhibitor, as probe, we found more abundant presence of γ‐secretase binding sites in the liver, gastrointestinal tract, hair follicle, pituitary gland, ovary and testis, as compared to the brain. Local application of L658, 458 delayed vibrissal regrowth following whisker removal. These results suggest that γ‐secretase may execute important biological functions in many peripheral systems, as in the brain. The development of γ‐secretase inhibitors/modulators for AD and cancer therapy should include close monitoring of toxicological panels for hepatic, gastrointestinal, endocrinal and reproductive functions.